Towards Creating a Global Urban Toponymy—A Comment - Liora Bigon (Urban Science, 2020)
This commentary points to the problems inherent in critical place names studies in terms of classic research topics, methodologies and geographies. It expounds the limits of the official “index”, that is, the variety of traditional urban inscriptions on which critical toponymy scholars rely in interpreting modern urban spatialities—e.g., lists of street names, official street signage, gazetteers, archival materials, etc. The argument is that in Southern urban contexts, where informality in planning can reach up to about 80 percent of the city, researching official naming and signage renders a distorted image of the city and its namescape production. A comment is thus made on the need to embrace more innovative and almost ethnographic research methodologies for understanding place referencing, place attachment and everyday navigational channels in Southern cities. These will generate a more substantial contribution towards the creation of global urban toponymy and a further de-colonization of Eurocentric presumptions regarding governmentality, urban management, and the accompanying role of street naming systems.